2020
DOI: 10.1515/bmc-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant, anti-inflammatory and antiproliferative activities of the essential oil of Cymbopogon nardus, a plant used in traditional medicine

Abstract: AbstractObjectivesNatural products commonly used in traditional medicine, such as essential oils (EOs), are attractive sources for the development of molecules with anti-proliferative activities for future treatment of human cancers, e.g., prostate and cervical cancer. In this study, the chemical composition of the EO from Cymbopogon nardus was characterized, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…Dihydrocapsaicin berpotensi sebagai inhibitor COX-2 dengan menstimulus penghambatan pada lima residu asam amino COX-2. Dihidrocapsaicin berpotensi sebagai inhibitor COX-2 menghambat kinerja sitokim pro inflamasi sebagai akibat dari diinduksi COX-2 (Bayala et al, 2020;Funk et al, 2016). Pada Tabel 3 terdapat residu asam amino LEU152 membentuk ikatan elektrostatik.…”
Section: Interaksi Molekuler Senyawa Dihydrocapsaicin Terhadap Cox-2unclassified
“…Dihydrocapsaicin berpotensi sebagai inhibitor COX-2 dengan menstimulus penghambatan pada lima residu asam amino COX-2. Dihidrocapsaicin berpotensi sebagai inhibitor COX-2 menghambat kinerja sitokim pro inflamasi sebagai akibat dari diinduksi COX-2 (Bayala et al, 2020;Funk et al, 2016). Pada Tabel 3 terdapat residu asam amino LEU152 membentuk ikatan elektrostatik.…”
Section: Interaksi Molekuler Senyawa Dihydrocapsaicin Terhadap Cox-2unclassified
“…The components and proportions found in the EOCN in this study (Table 1) do not correspond to those obtained by other respondents in the literature. Bayala et al (2020) while observing the chemical composition and biological activities of Cymbopogon nardus essential oil in a country of the African continent found citronellal (33.06%-19.56min), geraniol (28.40%-22,57min), nerol (10.94%-21.80min), elemol (5.25%-30.52min) and delta-elemene (4.09%-26.43min) as respective majoritarian and retention times, De Toledo et al ( 2016) in their study found that the OECN has citronellal (27.87%-12.54min), geraniol (22.77%-16.73min), geranial (14.54%-17.38min), citronellol (11.85%-15.60min), and nerol (11.21%-16.12min) as main constituents. Both authors consider that these variation of chemical compounds and retention times found in the EOCN may have occurred due to climatic differences, soil type, form of cultivation and geographic location.…”
Section: Inhibition Of Mycelial Growth (%)mentioning
confidence: 99%
“…The essential oil of the species Cymbopogon nardus (OECN) is used in the manufacture of cosmetics and perfumes, in addition to having shown antimicrobial action against Escherichia coli, Salmonella spp., Pseudomonas spp., Streptococcus spp., and beyond that, antioxidant, anti-inflammatory. The chemical composition of OECN is described in the literature with high content of geraniol and citronellal (Wei et al, 2013;Bayala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lemongrass or Cymbopogon citratus has been reported to contain some bioactive substances, such as alkaloids, flavonoids, steroid, and terpenoids. Bioactive compounds in lemongrass essential oil are geraniol, citral, citronellal, and citronellol [1][2][3][4]. Those compounds have functioned as antifungal, antioxidant, anti-inflammation, antidiabetic, antimicrobial, and anti-tumor [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The study adapted by in silico study. Several chemical substances, including 3,3, camphor, eugenol, curzerenem, and isoborneol, were retrieved from the PubChem database. The PyRx 0.8 was used to minimize and convert the sdf file to a pdb format file of ligands.…”
mentioning
confidence: 99%